Web Reasoning and Rule Systems 7th International Conference, RR 2013, Mannheim, Germany, July 27-29, 2013. Proceedings - Faber, Wolfgang; Lembo, Domenico; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 7th International Conference on Web Reasoning and Rule Systems, RR 2013, held in Manheim, Germany in July 2013. The 19 revised research papers and 4 technical communications presented together with 2 invited talks and 1 tutorial talk were carefully reviewed and selected from 34 submissions. The scope of conference is decision making, planning, and intelligent agents, reasoning, machine learning, knowledge extraction and IR technologies, large-scale data management and reasoning on the web of data, data integration, dataspaces and ontology-based data access, non-standard reasoning, algorithms for distributed, parallelized, and scalable reasoning, and system descriptions and experimentation.
Invited Talks -- Inconsistency Management for Description Logic Programs and Beyond -- Reasoning About Pattern-Based XML Queries -- Answer Set Programming: Language, Applications and Development Tools -- Full Papers -- A Variant of Earley Deduction with Partial Evaluation -- Verification and Synthesis in Description Logic Based Dynamic Systems -- Towards an Efficient Algorithm to Reason over Description Logics -- Extended with Nominal Schemas -- Computing Incoherence Explanations for Learned Ontologies -- An Ontology-Based Reasoning Approach for Electric Power Utilities -- Conjunctive Queries with Negation over DL-Lite: A Closer Look -- On the Exploration of the Query Rewriting Space with Existential Rules -- Incomplete Information in RDF -- RIO: Minimizing User Interaction in Ontology Debugging -- Eliminating Nonmonotonic DL-Atoms in Description Logic Programs -- BUNDLE: A Reasoner for Probabilistic Ontologies -- Technical Communications -- Detection of Inconsistencies in Rules Due to Changes in Ontologies: Let$1 (Bs Get Formal -- Rule Revision in Normal DL Logic Programs -- OBDA and Intermodal Logistics: Active Projects and Applications -- Semantic Pervasive Advertising -- Semantics for Mapping Relations in SKOS -- From OWL to DL-Lite through Efficient Ontology Approximation -- PQMPMS: A Preference-enabled Querying Mechanism for Personalized Mobile Search -- An Analyzer of Existential Rule Bases -- Stream Rule: A Nonmonotonic Stream Reasoning System for the Semantic Web.-An Integrated Environment for Reasoning over Ontologies via Logic Programming -- Horn-DL: An Expressive Horn Description Logic with PTime Data Complexity -- Parameter Learning for Probabilistic Ontologies.s
Keywords: Computer science; Software engineering; Logic design; Information systems; Data mining; Information storage and retrieval systems; Computer Science; Information Systems Applications (incl. Internet).; Information Systems and Communication Service; Information Storage and Retrieval; Data Mining and Knowledge Discovery; Software Engineering; Logics and Meanings of Programs